2010
DOI: 10.1111/j.1745-4565.2010.00240.x
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Colonization of Pu‐erh Tea in Yunnan

Abstract: Pu-erh tea is a popular beverage in Southeast Asia, especially in many areas of China. Natural fungal inoculation and fermentation form its special quality and function in health care. At the same time, a common assumption is that unknown fungi from natural inoculation may pose a risk for safety of drinking the beverage, leading to an urgent need for a thorough fungal survey of Pu-erh tea. The present paper reports the natural fungal colonizations isolated from 60 representative samples. The results of the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 20 publications
5
39
1
Order By: Relevance
“…Most researchers think that fungi, including species of Aspergillus , Fusarium , Penicillium , Rhizomucor , Trichoderma , Cladosporium and Mucor , and yeasts are likely to be key players responsible for puer tea fermentation . In comparison with those previous research data, we found significantly lower percentages of Eukaryota in the present puer tea metagenomic analysis; instead, the dominant microbes were bacteria.…”
Section: Discussioncontrasting
confidence: 80%
“…Most researchers think that fungi, including species of Aspergillus , Fusarium , Penicillium , Rhizomucor , Trichoderma , Cladosporium and Mucor , and yeasts are likely to be key players responsible for puer tea fermentation . In comparison with those previous research data, we found significantly lower percentages of Eukaryota in the present puer tea metagenomic analysis; instead, the dominant microbes were bacteria.…”
Section: Discussioncontrasting
confidence: 80%
“…The number of fungi detected in both raw and ripened tea declined as the aging period increased (Figure ). The piling or fermentation of the ripened Pu'er tea before it is compressed into bricks may increase fungal multiplication (Zhao and others ). The decline in fungal numbers with aging may result from a decrease in water content (Peng and Yu ) or a limited availability of nutrients as the proportion of less accessible compounds and more recalcitrant compounds increases with decomposition.…”
Section: Resultsmentioning
confidence: 99%
“…Pu'er, a unique postfermented tea produced in China, has antiobesity, hypolipidemic, and antioxidative properties (Duh and others ; Chiang and others ; Jie and others ; Wu and others ; Mo and others ). Pu'er tea is now commonly consumed in Southeast Asia and western countries as raw tea (similar to green tea) or ripened (fermented) tea (Zhao and others ). The processing of raw tea includes sun fixation, rolling, and sun drying before the tea is compressed into tea bricks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…and Penicillium spp. are the filamentous fungal genera commonly associated with SSF of pu-erh tea [52][53][54], particularly A. niger, A. sydowii and A. tamarii having been widely reported as the dominant fungi in the SSF of pu-erh tea. The assessment in agar mediums with theophylline as carbon source showed that six Aspergillus isolates could survive in theophylline agar mediums, which suggested that those six candidate isolates (Table 3) could utilize theophylline as potential carbon source directly in the absence of other carbon source.…”
Section: Discussionmentioning
confidence: 99%